2015
DOI: 10.1111/bcpt.12473
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Patients at High Risk of Medication Errors: Development and Validation of an Algorithm

Abstract: Medication errors (MEs) are preventable and can result in patient harm and increased expenses in the healthcare system in terms of hospitalization, prolonged hospitalizations and even death. We aimed to develop a screening tool to detect acutely admitted patients at low or high risk of MEs comprised by items found by literature search and the use of theoretical weighting. Predictive variables used for the development of the risk score were found by the literature search. Three retrospective patient populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
119
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(131 citation statements)
references
References 34 publications
5
119
0
7
Order By: Relevance
“…Patient safety, particularly medication safety, has become a focus of worldwide attention (Huynh, Wong, Correa‐West, Terry, & McCarthy, ; Pawluk et al., ). Medication errors are one of the most common causes of patient injury; of these errors, 46% are preventable (Saedder et al., ; Smeulers et al., ). As direct practitioners and observers of drug treatment, nurses spend approximately 40% of their work time performing drug therapy (Kavanagh, ).…”
Section: Introductionmentioning
confidence: 99%
“…Patient safety, particularly medication safety, has become a focus of worldwide attention (Huynh, Wong, Correa‐West, Terry, & McCarthy, ; Pawluk et al., ). Medication errors are one of the most common causes of patient injury; of these errors, 46% are preventable (Saedder et al., ; Smeulers et al., ). As direct practitioners and observers of drug treatment, nurses spend approximately 40% of their work time performing drug therapy (Kavanagh, ).…”
Section: Introductionmentioning
confidence: 99%
“…Tools such as cardiac-risk calculators and the Waterlow score (to assess the risk of pressure ulcers) are both used daily across the NHS. 31 32 Prediction tools to identify hospitalised patients at risk of adverse medication-related outcomes have been developed, 33–41 but the majority identify patients at risk of adverse drug reactions, 34 35 adverse drug events 36 or medication errors, 37 rather than MRPs, or are based on ‘expert opinion’ rather than statistical determination. 38–41…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has identified medicines that are potentially high‐risk when used in a hospital inpatient setting, but direct comparison between sources is difficult due to differences in study design, outcome measures, and the way medicines were grouped. To our knowledge, the present study is the first to identify high‐risk medicines that are associated with moderate or severe preventable MRPs.…”
Section: Discussionmentioning
confidence: 99%
“…High‐risk medicines were grouped into 11 categories (Table ), selected based on previously published research . Grouping was used rather than considering medicines individually since different organisations are likely to use different specific medicines.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation